IRAN ON THE WAY TO INTEGRATION WITH CENTRAL ASIAN COUNTRIES - А.М., Чокaтовa (Journal of Oriental Studies, 2019)
The purpose of this article is develop of trade between Iran and the countries of Central Asia, iden- tifying trends in economic integration and potential problems. Research methodology - this scientific study used the general scientific principles of knowledge of economic phenomena: systems, expertise, synthesis, and economic and statistical analysis, methods of deduction and induction, as well as practical empirical methods. The relevance of the article is the dynamics of the development of the economic partnership of Iran with the countries of Central Asia, mutually beneficial trading and investment plans. This article is devoted trade relations between Iran and the countries of Central Asia, the integration processes of economic relations and its advantages and opportunities for the region. Indeed, one of the features of globalization - regional convergence, integration and membership in international organizations will be aimed at the globalization of trade and the interaction of states in order to eliminate various customs barriers. The relations of the countries of the region with the Islamic Republic of Iran, which have grown significantly in the region after independence of the Central Asian states, including trade and economic ties, are also considered. The main areas of cooperation were the conclusion of certain invest- ment agreements with investors and Kazakhstan transnational companies, which provided for specific measures of state support for the largest and priority investment projects, as well as further measures to develop these projects. These events, along with the economic potential of the two countries, have a strong influence on regional and global economic growth. This is evidenced by the words of our Presi- dent N. A. Nazarbayev: “The absolute priority in ensuring national security will be given to our foreign policy, our foreign economic relations and the solid position of Kazakhstan with its neighbors, countries of the region and the leading nations of the world.” Key words: regional, transnational, regional convergence, regional integration.